Image Data Software Component Design and Development for Faster Image Processing - Okky Putra Barus; Robin Robin (Jurnal Mantik, 2020)
Most software engineers rely too much on the operating system (OS) built-in software components when developing software. The Bitmap software component is one of those software component classes which is mostly used when developing a software which required to view image which has already provided by the Windows OS. Therefore, using the Bitmap component to process image digitally required longer time to accomplished compares to a very simple image processing software such as Microsoft Paint itself and other image processing tools. This problem has indicated that the Bitmap component isn't suitable and not reliable for the software engineers to develop any software which required image processing in their software. In this research, this problem can be solved by designing a new image software component which is so-called as image data which was designed for faster image processing ever. From the experiment result, the image data component can process a digital image a lot faster for about 19 times than the Bitmap component do. By using the image data software component which can process a digital image faster than the built-in Bitmap component can provide the engineer to develop a more reliable and higher performance rather than using the Bitmap component in their software.